1999
DOI: 10.1103/physrevlett.82.3320
|View full text |Cite|
|
Sign up to set email alerts
|

Crossover from Fermi Liquid to Wigner Molecule Behavior in Quantum Dots

Abstract: The crossover from weak to strong correlations in parabolic quantum dots at zero magnetic field is studied by numerically exact path-integral Monte Carlo simulations for up to eight electrons. By the use of a multilevel blocking algorithm, the simulations are carried out free of the fermion sign problem. We obtain a universal crossover governed only by the density parameter r s . For r s . r c , the data are consistent with a Wigner molecule description, while, for r s , r c , Fermi liquid behavior is recovere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
231
2
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(262 citation statements)
references
References 21 publications
16
231
2
1
Order By: Relevance
“…The height of the QD can additionally influence this critical diameter, as a smaller electronhole separation leads to a stronger lateral confinement of the holes by the attraction of the electrons. Prior two-dimensional studies of electron interactions in QDs [36][37][38][39][40] raised the question whether a Wigner molecule (of electrons) is reliably described within the unrestricted Hartree-Fock method, allowing for symmetry-broken solutions 41 . Our study uses such a (here three-dimensional) Hartree-Fock method (see the Simulation Methods subsection), which predicts a Wigner molecule-like hole separation within the hybrid-XX model.…”
Section: Resultsmentioning
confidence: 99%
“…The height of the QD can additionally influence this critical diameter, as a smaller electronhole separation leads to a stronger lateral confinement of the holes by the attraction of the electrons. Prior two-dimensional studies of electron interactions in QDs [36][37][38][39][40] raised the question whether a Wigner molecule (of electrons) is reliably described within the unrestricted Hartree-Fock method, allowing for symmetry-broken solutions 41 . Our study uses such a (here three-dimensional) Hartree-Fock method (see the Simulation Methods subsection), which predicts a Wigner molecule-like hole separation within the hybrid-XX model.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by the discovery in the case of electrons of REMs at high B (and from the fact that Wigner molecules form also at zero magnetic field [28,29,30,31,32,33]) some theoretical studies have most recently shown that analogous molecular patterns of localized bosons do form in the case of a small number of particles inside a static or rotating harmonic trap [34,35,36,37,38]. In analogy with the electron case, the bosonic molecular structures can be referred to [36] as rotating boson molecules (RBMs); a description of RBMs via a variational wave function [39] built from symmetry-breaking displaced Gaussian orbitals with subsequent restoration of the rotational symmetry was presented in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…We close with a caveat and a comment: First, this work is based on the 2D local spin density approximation whose validity, though already verified for small parabolic QD's [29,30], is not well tested for large non-parabolic quantum dots as studied here. Our result highlights the need to go beyond RPA-RMT and perform a real Fermi liquid theory study.…”
mentioning
confidence: 99%
“…We use the standard local spin density approximation (LSDA) for E xc which works well in various semiconductors; in particular, we use Tanatar and Ceperley's 2D parametrization [28]. For 2D clean QDs, comparisons with quantum Monte-Carlo calculations for N ≤ 8 and interaction strength parameter r s ≤ 8.0 have shown that LSDA works well for both the ground state spin and energy [29,30].…”
mentioning
confidence: 99%